RANDOM WALK THEORY APPLIED TO DAPHNIA MOTION - KOMIN, NIKO; ERDMANN, UDO; SCHIMANSKY-GEIER, LUTZ (Fluctuation and noise letters, 2004)
The zooplankton Daphnia or "water flea" — one of the most common crustacean to be found in freshwater — is subject to recent studies. It is known to perform vortex motions under certain light conditions as well as more complex navigational tasks. Experimental data show that Daphnia move with a preferred turning angle, what is of main interest in this paper. The above-mentioned experimental fact is taken in order to derive a diffusion law for these types of motion. Deviations from the free diffusive behavior are investigated, based on random walk theory.